Basic care procedures [ showering and bed-bathing (Video Education Australasia / New Zealand Pty Ltd, 2006)
Maintaining personal hygiene plays an important role in preventing disease, especially infection; as well as contributing to the patient's general well-being, preserving comfort and positive body image. This program demonstrates how to carry out basic care procedures of showering and bed bathing in a professional and caring manner. The general care principles of safety, privacy and comfort are highlighted throughout the program